2015
DOI: 10.1186/s40411-014-0015-5
|View full text |Cite
|
Sign up to set email alerts
|

Revealing influence of model structure and test case profile on the prioritization of test cases in the context of model-based testing

Abstract: Background: Test case prioritization techniques aim at defining an order of test cases that favor the achievement of a goal during test execution, such as revealing failures as earlier as possible. A number of techniques have already been proposed and investigated in the literature and experimental results have discussed whether a technique is more successful than others. However, in the context of model-based testing, only a few attempts have been made towards either proposing or experimenting test case prior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Empirical study [24] performed by João Felipe Silva Ouriques et al investigates the effect of the model structure and characteristics of test cases that fail on the fault detection capability of several TCP techniques. Study results show that the characteristics of failed test cases affect the investigated techniques more significantly than the model layout.…”
Section: Related Workmentioning
confidence: 99%
“…Empirical study [24] performed by João Felipe Silva Ouriques et al investigates the effect of the model structure and characteristics of test cases that fail on the fault detection capability of several TCP techniques. Study results show that the characteristics of failed test cases affect the investigated techniques more significantly than the model layout.…”
Section: Related Workmentioning
confidence: 99%
“…3.2 Redundancy [12] stated that a large number of test cases may caused redundancy. The sequence of an event test case can produce a large test size since it is the behaviour of the event sequence test case to have large input of sequences, which can sometimes be infinite.…”
Section: Lines Of Codesmentioning
confidence: 99%
“…To the best of our knowledge, there is no other initiative of applying ARP in the MBT context. In previous work, we conducted a set of studies, as already discussed in Section 1 [21] including the two variants, with Jaccard [11] and Manhattan [22] distance functions. Besides our main results, in the referred context, Jaccard function performed better than the Manhattan.…”
Section: Related Workmentioning
confidence: 99%
“…In a previous work [21], we performed a set of empirical studies evaluating how several factors, such as number of faults, elements of model's layout (represented by the amount of branches, joins, and loops it has), and failing test cases' characteristics, can affect the behavior of traditional TCP techniques in the MBT context, focusing on Labeled Transition Systems (LTS). Our results showed that, for models with different layouts, the investigated techniques did not present variation in fault detection capability, which indicates low effects of model layout.…”
Section: Introductionmentioning
confidence: 99%